Left ventricular dysfunction, heart failure, and mortality risk factors in de novo pacemaker recipients and those requiring pacemaker generator replacement. (3rd October 2022) - Abdul Samad, N H; Lowry, J E; Cole, C A; Straw, S; Gierula, J; Witte, K K; Paton, M F
Abstract: Background: Pacing the right ventricle (RV) can lead to adverse remodelling of the left ventricle (LV), LV dysfunction, increased risk of heart failure hospitalisation (HFH) and mortality. Despite RV pacing avoidance programming becoming commonplace, pacemaker patients remain at risk of pacing-induced cardiomyopathy. New pacing strategies and cardiac resynchronisation therapy are available therapeutic options, but it is unclear which patients should be targeted, and when. Purpose: This study examined the effects of RV pacing on LV function, the risk of heart failure requiring hospitalisation and all-cause mortality in patients during the first 12 months of pacemaker therapy, compared to those at pacemaker generator replacement (PGR). Methods: Data were obtained from a cohort of patients who underwent de novo pacemaker implantation between 2014 and 2017, and patients requiring PGR between 2008 and 2011 at a single tertiary UK hospital, with follow-up from 12 months. Clinical, echocardiographic, and pacemaker variables, medication, and past medical history data were collected. Predictors of a combined endpoint of all-cause mortality or HFH were assessed using cox-regression analysis, with predictors of impaired LV function analysed using multivariable regression analysis. Results: 514 newly implanted (NI) patients (mean age, 75 years; 66% male) were recruited, and 491 patients (mean age, 76 years; 56% male) requiring PGR. After a mean follow up of 887 days, 79 NI patients (16%) were deceased (n=27) or had been hospitalised for HF (n=52), whereas after a mean follow up of 668 days, 56 patients after PGR (12%) were deceased (n=34) or had been hospitalised (n=22) for HF. After 12 months of pacemaker therapy, 182 (35%) NI patients had a LV ejection fraction (LVEF) <50%, which had a higher incidence at PGR of 197 (40%). Age was the only significant predictor of mortality or HFH for both NI and PGR (hazard ratio (HR), 1.068; 95% confidence interval (CI), 1.039 to 1.098; p<0.001 vs 1.035; 95% CI, 1.007 to 1.064; p=0.014), respectively). Univariate analysis revealed baseline LVEF (2.439; 95 percent CI, 1.279 to 4.659; p=0.007), RV pacing burden, medication and blood chemistry were significant predictors of the combined outcome at PGR but not at NI (Table 2). Multivariable analysis of predictors of LV impairment (<50% LVEF) showed history of MI (odds ratio (OR), 0.47; 95% CI, 0.29 to 0.78; p=0.003), RV pacing burden (1.01; 95% CI, 1.01 to 1.02; p<0.001) and creatinine (1.06; 95% CI, 1.02 to 1.10; p=0.004) were independently associated in both cohorts. Conclusions: Our data suggest that there remains a similar subgroup of people from initial implantation to PGR at risk of LV impairment that might benefit from medication optimisation or novel pacing strategies. Further research is required to better identifying these people to direct more complex therapies to those with the most to gain. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The research is supported by a National Institute for Health Research (NIHR) clinician scientist fellowship (NIHRCS-2012-032). The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health. This research was supported by the NIHR Leeds Clinical Research Facility.